Retinoblastoma binding protein 4 maintains cycling neural stem cells and prevents DNA damage and Tp53-dependent apoptosis in rb1 mutant neural progenitors - Schultz-Rogers, Laura E; Almeida, Maira P; Wierson, Wesley A; Kool, Marcel; Mcgrail, Maura (bioRxiv, 2018)
Retinoblastoma-binding protein 4 (Rbbp4) is a WDR adaptor protein for multiple chromatin remodelers implicated in human oncogenesis. Here we show Rbbp4 is overexpressed in zebrafish rb1-embryonal brain tumors and is upregulated across the spectrum of human embryonal and glial brain cancers. We demonstrate in vivo Rbbp4 is essential for zebrafish neurogenesis and has distinct roles in neural stem and progenitor cells. rbbp4 mutant neural stem cells show delayed cell cycle progression and become hypertrophic. In contrast, rbbp4 mutant neural precursors accumulate extensive DNA damage and undergo programmed cell death that is dependent on Tp53 signaling. Loss of Rbbp4 and disruption of genome integrity correlates with failure of neural precursors to initiate quiescence and transition to differentiation. rbbp4; rb1 double mutants show that survival of neural precursors after disruption of Rb1 is dependent on Rbbp4. Elevated Rbbp4 in Rb1-deficient brain tumors might drive proliferation and circumvent DNA damage and Tp53-dependent apoptosis, lending support to current interest in Rbbp4 as a potential druggable target.